Methods and Techniques of Teaching Grammar in ELT - Supriusman Supriusman (Universitas Negeri Padang, 2014)
One of several factors that makes students successful in learning English as a foreign language is determined by the methods and techniques used by the English teachers in English language teaching. Of course, the methods and the techniques applied by the teachers in the classroom vary from one teacher to another teacher. In addition, the methods and techniques used rely on the language skills and language components, the objective of teaching and learning designed, students’ English proficiency levels as well as the teachers’ knowledge and experience in implementing the methods and techniques used when teaching and learning takes place in the classroom. Grammar as one of the language components has an important role to play to support the students to be able to learn and use productive skills (speaking and writing), and receptive skills (listening, and reading). Therefore, this paper limits its discussions on methods and techniques used in teaching Grammar in ELT. In this paper, the writer will discuss the definitions of methods, techniques, teaching and how the teachers apply them practically in the classroom. It is expected that this paper is useful not only to increase the quality of English teachers but also the quality of students or graduates from the schools.